Asynchronous Cell Cycle and Asymmetric Vacuolar Inheritance in True Hyphae of Candida albicans - Barelle, Caroline J. (American Society for Microbiology, 2003)
Candida albicans forms unconstricted hyphae in serum-containing medium that are divided into discrete compartments. Time-lapse photomicroscopy, flow cytometry, and a novel three-dimensional imaging system were used to demonstrate that the kinetics and cell cycle events accompanying hyphal development were correlated with dynamic changes in vacuole morphology and the pattern of vacuole inheritance. Apical cells of hyphae underwent continuous extension before and after the first cytokinesis event. However, the resulting mother cell and sub-apical compartments did not immediately reenter the cell cycle and instead underwent cell cycle arrest before reentering the cycle. Vacuole was inherited asymmetrically at cytokinesis so that the distal, arrested compartments inherited most vacuole and the growing apical cell inherited most cytoplasm. Hydroxyurea release experiments demonstrated that the arrested, vacuolated hyphal compartments were in the G(1) phase of the cycle. The period of cell cycle arrest was decreased by the provision of assimilatable forms of nitrogen, suggesting that the hyphal cell cycle is regulated by nitrogen limitation that results in sup-apical cell cycle arrest. This pattern of growth is distinct from that of the synchronous, symmetrical development of pseudohyphae of C. albicans and other yeast species. These observations suggest that the cellular vacuole space correlates with alterations in the cell cycles of different cell types and that the total organelle space may influence size-regulated functions and hence the timing of the eukaryotic cell cycle.